PREVENTION OF COMPLICATIONS OF OPEN FRACTURES OF THE TIBIA IN PATIENTS WITH MULTIPLE AND COMBINED TRAUMA (Multidisciplinary Journal of Science and Technology, 2025)
Open fractures of the tibia are among the most challenging injuries in orthopedic and trauma surgery due to their high risk of infection, delayed bone healing, and soft tissue complications. The complexity increases significantly when they occur in patients with multiple or combined trauma, where systemic physiological responses, poly-organ damage, and prolonged immobilization create additional risks. This article examines the biological and clinical mechanisms underlying complications in open tibial fractures, identifies major risk factors, and reviews evidence-based strategies for their prevention. Emphasis is placed on early multidisciplinary management, optimized debridement, infection control, stabilization techniques, and modern reconstructive approaches aimed at preserving limb function and reducing disability rates.